Challenges in Early Diagnosis of Oral Cancer: Cases Series - Nanditha Sujir; Junaid Ahmed; Keerthilatha Pai; Ceena Denny; Nandita Shenoy (University of Zagreb. School of Dental Medicine, 2019)
Oral cancer has an overall survival rate of only 50%. This prognosis is significantly improved when this disease is diagnosed and treated in its early stages. Oral cancer is usually associated with classical clinical features associated with malignancy resulting in accurate diagnosis. However, certain cases of oral cancer, especially in its early stages, can be clinically deceptive and can be misdiagnosed. There is a recent trend of changing demographics and etiology associated with oral cancer adding to the diagnostic challenges faced by the clinician. The awareness of these changing trends is needed to aid in early diagnosis of oral cancer. In this case series, we have presented three cases of patients with challenging aspects.